Self Marketing Lansia-Preneur melalui Pendekatan Symbolic Interactionism di Lumajang - Nur Latifa Isnaini Putri (Airlangga Journal of Innovation Management, 2022)
The complexity of the needs requires everyone to work and make the right decisions in meeting the needs in order to ensure an effective and decent life. Self marketing is one of the efforts that can be done by an elderly person to support daily needs. This study aims to determine the meaning of the elderly entrepreneurial activity and to determine the self-marketing pattern of elderly-preneurs in Lumajang. This type of research is a descriptive qualitative research. Determination of informants in the study using purposive sampling method. The data analysis method uses four steps, there are data collection, data condensation, data presentation, and conclusions. This study concludes that there are various meanings of entrepreneurship for elderly including entrepreneurship as a fulfillment of economic needs, as a form of health resilience and as worship. As for the pattern of self-marketing that was found, as an optimization of symbols in influencing consumer behavior, place of business as a support for contrasting social class images, and the linearity of elderly products with local and traditional products. This research is expected to be a reference for science in field of inclusive marketing and as a reference for Government to improve an elderly friendly environment in Lumajang.